Selection of Paspalum accessions for use in poorly drained soils - L. M. Benez; P. M. Santos; A. P. Fávero; J. C. G. Santos; G. C. Ferreira; A. A. F. Garcia (Brazilian Journal of Biology)
Abstract Excess soil water can result from inadequate drainage, seasonal groundwater fluctuations, and extreme rainfall events. Diversifying forage species is a key strategy for mitigating these challenges. This study aimed to evaluate Paspalum germplasm collected from different regions of Brazil and identify accessions with potential for use in poorly drained environments. A total of twenty-three Paspalum accessions were assessed under two water regimes (flooded and non-flooded), alongside Urochloa brizantha cv. Marandu, in a randomized block design with a 24 × 2 factorial arrangement and three replications. The experiment was conducted in a greenhouse using potted plants. The evaluated traits were dry mass of leaves, stems, dead material, aerial biomass, roots, the ratio of dead material dry mass to aerial biomass, leaf area, number of tillers, and leaf elongation. Data were subjected to analysis of variance and a means comparison test at a 5% significance level, followed by biplot analysis. All genotypes were affected by flooding; however, BGP238, BGP112, and BGP410 exhibited superior performance in the assessed growth and biomass production traits compared to U. brizantha cv. Marandu under both flooded and non-flooded conditions. These genotypes can advance in plant breeding studies.